Химические мутагены в селекции цветочно-декоративных растений - Кудина, Г.А. (Промышленная ботаника, 2006)
Results of the effect of diethylsulfate (DES), dimethylsulfate (DMS), nitrosoethilcarbamide (NEC), nitrosomethylcarbomide (NMC) on seeds and vegetative organs of flower-ornamental plants are considered. Suppressive action of the NMC and NEC studied doses on seed germination and seedling viability of the most of researched species of flower-ornamental plants is determined. Perceptible, average stable, and firm species are pointed out by genotyp reaction on mutagens effect. Spectrum of biomorphologic changes of flower-ornamental plants under mutagens effect is given.